Biological control of mosquitoes with odonates: A case study in Guyana - Cindy Marina Dasrat; Gyanpriya Maharaj (Smujo International, 2021)
Abstract. Dasrat CM, Maharaj G. 2021. Biological control of mosquitoes with odonates: A case study in Guyana. Nusantara Bioscience 13: 163-170. Mosquitoes have plagued the lives of tropical residents as pests. However, due to their role as vectors of life-threatening diseases, controlling their population is necessary, especially in areas of prevalence – the Caribbean and Equatorial regions. In Guyana, we employ chemical treatments sub-regionally to eradicate mosquitoes. However, this treatment has limited success and is harmful to the environment. Therefore, our study focused on an environmentally friendly method such as biological control. This study was conducted at the University of Guyana, Turkeyen campus, where we exploited Odonata, Anisoptera, and Zygoptera as natural predators of mosquitoes of the genus Culex. The feeding efficiency and behaviors of naiads from the Libellulidae and Coenagrionidae families were assessed from April to May 2018. Each naiad was fed three Culine pupae and larvae, then observed for 60 minutes. We found that both groups pursue soft-bodied larvae and Libellulidae naiads are more efficient predators due to the higher feeding rate than Coenagrionidae. This finding is related to a behavioral study where we observed Libellulidae as active hunters that masticate and consume faster than Coenagrionidae, which lay-and-wait, opportunistic predators that swallow their prey. We concluded that Libellulidae is an efficient predator of mosquito larvae of the Culex genus, and we found a link between morphologic characteristics and feeding behaviors. We hope to use these results as a baseline study to develop mosquito biological control in Guyana. These can be used to reduce mosquito populations and the occurrence of vector diseases, as well as improve integrated pest and vector management.